Healthcare Workers’ General Health and Its Relation with Anxiety, Anger, and Posttraumatic Stress Disorder during COVID-19 Outbreak in Southeast Iran - Alireza Malakoutikhah; Leila Ahmadi Lari; Pooya Baharloo; Rasmieh Al-Amer; Mohamed Alnaiem; Hossein Khaluei; Mahlagha Dehghan (Mental Illness)
Background. Healthcare workers during the COVID-19 pandemic played an effective role in providing preventive and curative measures. Scientific evidence confirmed that the outbreak of this disease has caused numerous psychological problems such as pre- and posttraumatic stress disorder (PTSD), anxiety, depression, and anger at a global level. This study is aimed at investigating the general health of healthcare workers and its relationship with anxiety, anger, and posttraumatic stress disorder during the outbreak of COVID-19. Methods. This research was a cross-sectional study conducted on 455 healthcare workers of four teaching hospitals in Kerman, southeast of Iran. The convenience sampling method was used. The research tools included the 12-Item General Health Questionnaire (GHQ-12), the Impact of Event Scale-Revised (IES-R), the trait anxiety section of State-Trait Anxiety Inventory (STAI), and the trait anger section of Trait-State Anger Expression Inventory 2 (STAXI-2). Data analysis was done in IBM SPSS Statistics version 25 and using Pearson’s correlation tests, independent t-test, ANOVA, and multivariate linear regression. Results. 28.1% (n=128) of the participants had mental health disorders. The mean score of anxiety was 43.99±9.24 which was at moderate to high level of anxiety. The mean score of anger was 18.65±5.72 which was at the moderate level. The mean score of PTSD was 34.77±15.24 which was less than the midpoint of the questionnaire, i.e., the score of 44. The results of the multiple linear regression model that showed anxiety, anger, gender, and hospital were predictors of mental health (P<0.05). Conclusion. The results of the present study showed that about a quarter of the healthcare workers faced with the COVID-19 pandemic had mental health disorders and suffered from moderate to high anxiety, moderate anger, and PTSD. It was also observed in this study that there was a weak to moderate significant correlation between general health and anxiety, anger, and PTSD in healthcare workers. So, healthcare workers need a lot of social and psychological support.